1996
DOI: 10.1111/j.1476-5381.1996.tb16013.x
|View full text |Cite
|
Sign up to set email alerts
|

EndothelinB receptor‐mediated contraction in human pulmonary resistance arteries

Abstract: Using wire myography, we have examined the endothelin (ET) receptor subtypes mediating vasoconstriction to ET peptides in human pulmonary resistance arteries (150–200 μm, i.d.). Cumulative concentration‐response curves to ET‐1, sarafotoxin 6c (SX6c) and ET‐3 were constructed in the presence and absence of the selective antagonists FR 139317 (ETA‐selective), BMS 182874 (ETA‐selective) and BQ‐788 (ETB‐selective). All agonists induced concentration‐dependent contractions. However, the response curves to ET‐1 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 48 publications
4
55
0
2
Order By: Relevance
“…Other investigators, however, have reported a preferential increase in ETB receptors in pulmonary arteries of pulmonary hypertensive scleroderma patients [36]. Although both receptor subtypes mediate ET-1-induced contraction [37] and promote ETA and ETB expression was similar in normal and IPAH cell extracts.…”
Section: Discussionmentioning
confidence: 98%
“…Other investigators, however, have reported a preferential increase in ETB receptors in pulmonary arteries of pulmonary hypertensive scleroderma patients [36]. Although both receptor subtypes mediate ET-1-induced contraction [37] and promote ETA and ETB expression was similar in normal and IPAH cell extracts.…”
Section: Discussionmentioning
confidence: 98%
“…One in vitro study in isolated human pulmonary arteries [12] has demonstrated that stimulation of pulmonary arteries with ETBselective agonists (sarafotoxin 6c) resulted in ,25% of the constriction caused by native ET-1. In agreement with this, animal studies using selected concentrations of antagonists to the two receptor subtypes in small pulmonary vessels were able to show that, while single receptor antagonists to each of the two receptors produced some inhibition of ET-1-induced contraction, use of their combination to achieve comprehensive dual ETA and ETB receptor antagonism significantly inhibits ET-1-induced constriction (52¡5.3%, p,0.001; fig.…”
Section: Et-1 Mediates Its Effects Through Both the Eta And Etb Recepmentioning
confidence: 99%
“…In addition, upregulation of the ET-B receptor gene in the hyperplastic media of pulmonary arterial biopsies of CTEPH patients has been demonstrated. 12 ET-B receptor activation on smooth muscle cells is considered to contribute to vasoconstriction 13 and vascular remodeling. 14 Taken together, these observations indicate that ET-1 may also play a role in CTEPH, but so far no correlation with pathophysiology has been shown.…”
mentioning
confidence: 99%